Leveraging the Critical Incident Technique to Identify the Detrimental Effect of Cuscuta reflexa Roxb. on Dairy Animals - Shruti,; Madan Singh,; Braj Pal Singh, Shyamkumar T.S., Aneesha V. A., Dinesh Kumar, U. K. Dey, (Indian Journal of Extension Education, 2022)
The critical Incident technique was deployed to study the detrimental effect of Cuscuta reflexa on dairy animals. In the present study, the critical incidences were farmers’ fields where berseem was infested with Cuscuta reflexa and farmers were feeding that contaminated berseem to dairy animals. Thus, face-to-face interaction was done with 13 farmers of Malpur and Ganeshpur village of Bareilly district for the same incidences in the years 2021 and 2022. Based on farmers’ response it was observed that due to gradual feeding of berseem contaminated with Cuscuta reflexa on an average there was a reduction in milk yield of 5.35 L/day in 2021 and 3.35 L/day in 2022 of dairy animals. The annual economic loss was calculated as Rs. 27322/- in 2021 and Rs. 20048.57/- in 2022. The reduction in milk yield (68.67%) shares the maximum percentage of economic loss followed by replacement cost (25.38%), and then treatment cost (5.95%).